Transcriptome and miRNome Analysis Provide New Insight Into Host Lipid Accumulation, Innate Immunity, and Viral Persistence in Hepatitis C Virus Infection in vitro - Li, Chong; Lu, Lungen; Qi, Zhongtian; Zhu, Yongqiang; Su, Fengtao; Zhao, Ping; Dong, Hui (Frontiers in Microbiology, 2020)
Hepatitis C virus (HCV)-host cell interaction during infection disturbs cellular homeostasis and culminates in pathological consequences. The processes could be first embodied in gene expression of HCV-infected cells. Here, we investigated transcriptome and miRNA expression (miRNome) alterations in HCV-infected Huh7 cells at 12, 36 and 60 h after infection to systematically explore host responses. The number of deregulated genes in the HCV-infected cells increased with infection duration. The altered biological processes at 36 h were mainly associated with stress and inflammatory response, whereas the most enriched processes at 60 h were predominantly linked to lipid metabolism. Notably, the key genes that participated in lipogenesis were downregulated, and conversely, the genes implicated in fatty acid beta-oxidation were upregulated. Reduced expression of the key genes involved in lipoprotein assembly and secretion pointed to a decreased requirement for and export of lipids, leading to lipid accumulation in HCV-infected hepatocytes. Fluctuation in the expression of host factors, innate immunity genes and transcription factors provided insight into host-directed mechanisms to control viral replication. Furthermore, miRNome presented a comprehensive expression profile of miRNAs in HCV-infected Huh7 cells. The integrated analysis of transcriptome and miRNome suggested that deregulated miR-483, miR-1303, miR-1260a, miR-27a* and miR-21* directly regulated lipid metabolical genes at 60 h. The decreased miR-122 at 60 h was indirectly involved in lipid metabolism and is expected to attenuate rampant replication of HCV and potentially contribute to viral persistence. Our results will help to gain a comprehensive understanding of the molecular mechanisms implicated in HCV-induced pathogenesis.